Xirê : troca, fluxo e circulação do axé como forma de manutenção da sociabilidade no candomblé - Rosa Júnior, Juracy de Arimatéia (2018)
This work aims to identify how the processes of exchange in the public rituals of candomblé, more precisely in the xirês (festivities of worship to orixá), interfere in the maintenance of sociability and the circulation of axé. Analyzing the xirê from the theoretical reference interactionist, whose thinking is centered on non-utilitarian exchange, the research concludes that, in candomblé, there is an intricate system of exchanges that favors the interaction between practitioners and this system is maintained by factors such as: the need for socialization; the attribution of meaning that the festive calendar gives the members of candomblé and the circularity of the gift. The proposal was to do a study of xirê, ritual whose core is in the interaction between humans and gods, between humans and humans and still between gods and gods. In the xirê, the exchange is seen as a central and perennial element during the rite. In this perspective, the ethnographic data produced in the field revealed disagreements between the individualist western way of life and the community way of life of candomblé’s houses. From the methodological point of view, this is an investigation of ethnographic approach, of Olubajé's study. Although there are academic papers on the subject of candomblé, this research proposes a look from the Sciences of Religion, with the production of knowledge, allowing to clarify a subject not sufficiently investigated within the scope of the religious phenomenon in Brazil. In addition to its relevance and breadth, the present study intends to be an innovative contribution in the line of research that involves the Brazilian religious field, making possible to understand subjects that permeate the decisive role of religions of African matrix in the constitution of the socio-cultural identities of the country and in human relations and social. This research can contribute still bringing new concepts and new forms of understanding of the reality in the theme of religions of African matrix.